Effects of bone morphogenetic protein‐4 (BMP‐4) on adipocyte differentiation from mouse adipose‐derived stem cells. (21st July 2013) - Wei, X.; Li, G.; Yang, X.; Ba, K.; Fu, Y.; Fu, N.; Cai, X.; Li, G.; Chen, Q.; Wang, M.; Lin, Y.
Abstract Objectives As mesenchymal stem cells (MSCs) can be isolated easily from adipose tissues while retaining their self‐renewal and multi‐potential differentiation capacities, they hold promising possibilities for being applied extensively in tissue engineering. Bone morphogenetic protein (BMP) family members have been reported to provide instructive signals to MSCs for them to differentiate into several different cell lineages. The study described here aims to investigate whether BMP‐4 could promote adipose‐derived stem cell (ASC) differentiation into adipocytes under various concentrations. Materials and methods ASCs were isolated from mouse inguinal adipose pads and cultured in vitro. 10 ng/ml and 50 ng/ml BMP‐4 were added to adipogenic media for 8 days. Oil red‐O staining, reverse transcription/polymerase chain reaction and immunocytofluorescence staining were performed to examine differentiation of the ASCs. Results As indicated by increased expression of adipogenic and lipogenic genes (PPAR‐γ, APN and LPL) and proteins, 50 ng/ml BMP‐4 seemed to induce mASCs to differentiate into the adipo‐lineage compared to 10 ng/ml BMP‐4, and control groups. In addition, lipid droplets accumulated within the adipocytes under 50 ng/ml BMP‐4 stimulation, as shown by oil red‐O staining. Conclusions Our present study suggests that BMP‐4, as an adipo‐inducing factor, promoted adipogenesis of ASCs at higher concentrations (50 ng/ml) and can perhaps be considered as a candidate for use in adipose tissue engineering.